Expediting decarbonization in energy, waste, and water sector through digitalization in sustainable smart cities (SSC): Case-studies in Malaysia and China based on Industry 5.0 paradigm - Goh, Kai Chen; Tonni Agustiono, Kurniawan; Nadzirah, Zainordin; Ika Diyah Candra, Arifah; Muhamad Azahar, Abas; Md Asrul Nasid, Masrom; Sulzakimin, Mohamed; Roshartini, Omar; Khoo, Sui Lai; Gui, Hun Chuen; Toh, Tien Choon; Onn, Choo Wou (Elsevier Science, Ltd., 2024)
This work explores the application of Industry 5.0 principles in smart cities development in Malaysia and China, focusing on digital transformation for sustainable urban development. The study presents case-studies from both the countries, highlighting the implementation strategies, challenges, and outcomes associated with integrating advanced technologies to enhance efficiency, climate resilience, and sustainability. This study aims to develop a data-driven methodology to address the absence of region-specific frameworks for sustainable smart cities (SSCs) and to evaluate their impacts. In Malaysia, the implementation of smart energy management systems that utilize IoT and AI has shown promise in reducing carbon footprints and maximizing resource efficiency. China’s focus on smart water management using sensor networks and real-time data analytics provides insights into effective water conservation. Smart waste management systems have increased recycling rates by 20–30 %. Progress is crucial for the region’s pursuit of SSCs to reach a global investment of USD 2.5 trillion by 2025. This work concludes by discussing the implications of this work in both countries to achieve sustainable urbanization through Industry 5.0 technologies. This work offers recommendations for policymakers, urban planners, and technologists to navigate the complexities of smart city development, while providing a roadmap to leverage digital transformation to achieve decarbonization goals in energy, waste and water sector by 2060.